The West African Currency Board, 1912-1962 - Loynes, J. B.; Great Britain (London : West African Currency Board, 1962)
This book contains the report of the activities of the West African Currency Board to mark the fifty years of operation on the 21st November, 1962.
usc 12/11/18; 25/01/19
Loans
Keywords: Currency question; Africa, West